In vitro uptake of labeled triiodothyronine I-131 ion exchange resin as a thyroid function test - Pajuelo E., Alfonso (1968)
The triiodothyronine uptake test, was performed on 44 patients suffering from a variety of thyroid diseases plus 11 pregnant women, using this hormone labeled with I-131 and ionic exchange resin. Among the 44 patients there were 20 with thyrotoxicosis, 10 hypothyroid, 8 with diffuse non-toxic goiter and 6 with other thyroid conditions with no evidence of thyroid disfunction. An averange of 48,9% uptake for the hyperthyroid, 22,2% for the hypothyroid an 23,3% for the pregnant women was found. This gave a very significant difference from the normal group that averaged 32% according to a previous report. There was no difference between the normal group and the other two groups having no functional disturbance. Our results agree with the findingsof the other investigators in other countries. We think that this is a useful test adding a new parameter for the study of thyroid function. It is no necessary to administer radioactivity to the patient which is advantageous, and it is not modified by small doses of iodine compounds.